Financial performance analysis using value for money concept - Abdul Nasser Hasibuan (Junal Ilmu Manajemen, 2023)
The purpose of this study was conducted to find out how the financial performance of the North Padang Lawas Regency Social Service in social empowerment programs and handling the poor, social protection and security programs, and social rehabilitation programs is measured from the level of the economy, efficiency, and effectiveness. This research uses the descriptive quantitative method. Researchers use secondary data in the form of financial reports and primary data by distributing questionnaires. Data collection techniques are interviews, documentation, and questionnaires. The data is then analyzed using a value for money which consists of three elements, namely economy, efficiency, and effectiveness. The sampling technique used incidental sampling with a total sample of 105 respondents, then tested for validity and reliability to measure the reliability of the data. The results of this study indicate that the measurement of financial performance using the concept of value for money in social empowerment programs and handling the poor is included in the category of economical and efficient, but not yet classified as effective. Then the social protection and security program is included in the economical and efficient category, but not yet classified as effective. Whereas the social rehabilitation program is included in the economic category, it is not yet classified as efficient and not yet effective in achieving the target.